The Effect Of Giving Okra Fruit-Infused Water On Recreasing Cholesterol Levels In Hypercholesterolemia Patients In Payan Pabean Sidoarjo Village - Denis Farida; Heri Nur Cahyanto (Chakra Brahmanda Lentera Institute, 2022)
Background: In such a modern era, many experiencing society _ an inclined shift _ push for a change in the pattern of a healthy life, where many vote society _ for consuming food ready eat, eating fatty foods, and rarely sport. This _, if done in a manner that keeps going continuously for a period of long time _, will have an impact on the body, one of them i.e., the buildup of cholesterol. Study this aim to identify the influence of giving okra fruit-infused water to decline cholesterol in patients with hypercholesterolemia in hamlets pay customs Methods: The design study is a quasi-experiment with design non-equivalent control group design. With the use taking sample purposive sampling for one month. The population in the study is patients with hypercholesterolemia, with a sample study of as many as 32 people with 16 groups of treatment and 16 groups of control. Data collection using sheet observation and data analysis using paired t-tests. Infused water is given in 1 week. Results: A significance mark p 0.000, more diminutive than 0.05, is appropriate, with the base deciding the paired t-test. Conclusion: it concluded that there is an effect of okra fruit-infused water on a decline in cholesterol in patients with hypercholesterolemia in hamlets Payan Customs Sidoarjo